2018
DOI: 10.1039/c8ta00576a
|View full text |Cite
|
Sign up to set email alerts
|

Germanium-incorporated lithium silicate composites as highly efficient low-temperature sorbents for CO2 capture

Abstract: Germanium-incorporated lithium silicate nanostructures with exceptional carbon dioxide absorption kinetics and capacity in the temperature range of 150–700 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…synthesized samples of Li4SiO4 with Na substitution, forming Li3NaSiO4 that was able to carbonate and regenerate at lower temperatures than unmodified Li4SiO4. Another study of doping of the Si site with Ge also found enhanced CO2 absorption at temperatures < 450 °C, which was ascribed to lower barriers for Li ion diffusion caused by lattice expansion upon doping[478]. Similar effects have been seen for small amounts of alkali doping of the CaO-CaCO3 system leading to changes in the sintering behavior, with ionic mobility being enhanced through the creation of defects in the crystal lattice (Section 3.1.1).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…synthesized samples of Li4SiO4 with Na substitution, forming Li3NaSiO4 that was able to carbonate and regenerate at lower temperatures than unmodified Li4SiO4. Another study of doping of the Si site with Ge also found enhanced CO2 absorption at temperatures < 450 °C, which was ascribed to lower barriers for Li ion diffusion caused by lattice expansion upon doping[478]. Similar effects have been seen for small amounts of alkali doping of the CaO-CaCO3 system leading to changes in the sintering behavior, with ionic mobility being enhanced through the creation of defects in the crystal lattice (Section 3.1.1).…”
mentioning
confidence: 70%
“…Furthermore, the formation of oxygen vacancies also leads to changes in the overall crystal structure, often reducing barriers for Li ion diffusion, further compounding the overall increase in Li ion mobility.Following this work, a number of further studies have tried to purposely influence the rate of the ionic transport through structural modification to improve CO2 sorption properties. Subha and co-workers[478] synthesized a range of samples of the Li4SixGe1-xO4 solid solution, withx up to ~ 0.30. Samples with a Si:Ge ratio of 1:0.183 showed the most enhanced absorption capacity (324 mg g -1 ) and kinetics at both low and high absorption temperatures.…”
mentioning
confidence: 99%
“…89 Therefore, the incorporation of Ge in Li4SiO4 was considered as an option to enhance the kinetics and sorption capacity of Li4SiO4 sorbents. Subha et al 90 reported a facile synthesis strategy for Ge-incorporated Li4SiO4, and the assynthesized samples exhibited enhanced CO2 uptake and kinetics at 150-680 o C. For the sample with a Si : Ge molar ratio of 1 : 0.183, a sorption capacity of 32.4 wt% at the rate of 117 mg g -1 min -1 and a sorption capacity of 4.9 wt% at the rate of 36 mg g -1 min -1 were obtained at 680 and 300 o C (100 vol% CO2), respectively. This study demonstrated the possibility of employing Ge-incorporated Li4SiO4 to capture CO2 from chemical and petrochemical reactions in a wide temperature range, such as the WGS reaction that occurs at low temperature ranges of 150-450 o C, which is not possible with pure Li4SiO4.…”
Section: Si Substitutionmentioning
confidence: 99%
“…Subha et al 90 added a second phase (Y2O3, Gd2O3, and LaPO4) to prevent the sintering of Li4SiO4 at high temperatures. They demonstrated that the influence by the type of second phase on the CO2 capture performance was negligible when the composites were rich in sorbent (10:1 and 20:1 in sorbent/second phase), but became obvious when the second phase was higher (2:1).…”
Section: Incorporation Of Metal Oxide Componentsmentioning
confidence: 99%
“…To further improve the kinetics under low CO2 partial pressure conditions, doping of foreign materials [31,32], especially alkali carbonates [33,34], into Li4SiO4 particles has been studied. Zhang et al [35] and Seggiani et al [36] prepared K2CO3-or Na2CO3doped Li4SiO4 particles by means of a solid-state reaction.…”
Section: Introductionmentioning
confidence: 99%